Desain Air-Track Berbasis Sensor Infra-Red sebagai Media Pembelajaran Mekanika - Chairunnisa, Chairunnisa; Koen, Marwinda (Program Kreativitas Mahasiswa - Karsa Cipta, 2014)
On learning physics, many students are less understanding concept well.Students only memorization theory and formulas than understand the physics so its difficult to apply knowledge in daily life. Media of instruction designed can help students for creative thinking and discover patterns so that they could understand the subject matter well. Air track is one of the media that can be used for experimental mechanics of motion. However, the barriers are is the price of air track is an expensive. According to the survey of one of the producers of educational tools, a set of air track is prices reaches 10,5 million rupiah. The author intends to make the air track based infrared sensor as mechanic learning media that cheap and qualified. So that through these device, students can improve the understanding of the mechanics and physics learning interest. The methods used in the manufacture of air track design are prototype, preparation tools and materials, prototyping, testing and analysis, as well as finalization and completion. The results obtained with the prototype units with 3 components namely fotogate, gliders, air track support, series of electronic sensors and stopwatch, ackrilic, pulley and a spring System. Air track based infrared sensor worthy of use because the friction that occurs between the glider with air track very small (Âµ_k = 0.12). In addition, air track can be used as a device of teaching physics especially mechanics because it makes easy for students to understand the concepts, as well as the students were very interested to learn the mechanics of using the air track.Keywords : Air track, Media, Sensor